Red guava (Psidium guajava L) juice increases hemoglobin levels in female adolescent. - Tirtawati, Gusti Ayu; Kusmiyati, Kusmiyati; Rompas, Meivy; Terok, Maria; Runtu, Lorrien Grace; Fione, Vega Roosa; Adam, Yulien; Solang, Sesca Diana (Nutrición Clínica y Dietética Hospitalaria, 2025)
Background: One nutritional issue Indonesian adolescents face is micronutrient deficiency, with approximately 12% of male adolescents and 23% of female adolescents experiencing anemia, predominantly due to iron deficiency. Anemia in adolescent girls is particularly concerning as they are future mothers who will conceive and give birth, thereby increasing the risk of maternal mortality, preterm birth, and low birth weight. An initial survey of 7 female students revealed that 4 were anemic. This study aims to determine the effect of red guava juice on hemoglobin levels in female adolescents at a junior high school of SMP N 2 Belang, Belang District. Methods: This quasi-experimental study employed a pretest-posttest with control group design, involving a total sampling of 30 respondents divided into 15 respondents in the treatment group and 15 in the control group. Data were collected through observation sheets and analyzed using paired sample t-tests. Results: The paired sample t-test results indicated a significant effect of red guava juice on increasing hemoglobin levels in female adolescents, with a p-value of 0.002 and a mean value of 11.46 during the pretest and 12.58 during the posttest in the treatment group. In contrast, the control group, which did not receive any treatment, had a p-value of 0.334, indicating no significant increase in hemoglobin levels during the posttest. After consuming red guava juice, there was a considerable change from anemia to non-anemia. Conclusion: Adolescent girls consume red guava juice as an alternative to increasing haemoglobin levels.